Pengaruh Pendidikan Kesehatan Terhadap Tingkat Pengetahuan Anemia Pada Siswa SMK PP Negeri Sumedang - Amelia, Lienji; Della Afrilliani Sutaryo; Hani Siti Hasifa; Khoirunnisa Nabilatun Rofifah; Sari Oktavia Depyanti; Siti Fatimah Zahra; Dewi Dolifah; Delli Yuliana Rahmat (LPPM UNINUS, 2024)
Anemia is a serious health problem that affects society and is common throughout the world, especially in developing countries like Indonesia. The prevalence rate of anemia in adolescents aged 15 to 24 years is 32%, which means that 3-4 out of every 10 adolescents are estimated to suffer from anemia. This study aimed to determine the relationship between the level of knowledge about anemia and the incidence of anemia among adolescents. The method used in this community service is an educational method, namely health education about anemia. The result of this dedication is a change in knowledge after the provision of health education about anemia. Key Words: Anemia In Adolescents, Health Education, Level Of Knowledge